Summer crossing : a novel - Capote, Truman, 1924-1984. (New York : Random House, 2006)
Presents the classic novel by noted author Truman Capote about a young socialite, Grady McNeil, who is left alone in her parent's Fifth Avenue penthouse for the summer.
Kirkus Starred, November 2005
Adult
Adult
Kirkus Starred
Keywords: Manhattan (New York, N.Y.) -- Fiction; Manhattan (New York, N.Y.) -- Fiction; Love stories; Bildungsromans; Love stories; Bildungsromans